New frontiers of body composition in sport - Lukaski, H.; Raymond-Pope, C. J. (International Journal of Sports Medicine, 2021)
The body composition phenotype of an athlete displays the complex interaction among genotype, physiological and metabolic demands of a sport, diet, and physical training. Observational studies dominate the literature and describe the sport-specific physique characteristics (size, shape, and composition) of adult athletes by gender and levels of competition. Limited data reveal how body composition measurements can benefit an athlete. Thus, the objective is to identify purposeful measurements of body composition, notably fat and lean muscle masses, and determine their impact on the health and performance of athletes. Areas of interest include relationships among total and regional body composition measurements, muscle function, sport-specific performance, risk of injury, return to sport after injury, and identification of activity-induced fluid shifts. Discussion includes the application of specific uses of dual X-ray absorptiometry and bioelectrical impedance including an emphasis on the need to minimize measurement errors and standardize protocols, and highlights opportunities for future research. This focus on functional body composition can benefit the health and optimize the performance of an athlete.